2004
DOI: 10.1023/b:mcbi.0000012840.67616.cc
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule alteration is an early cellular reaction to the metabolic challenge in ischemic cardiomyocytes

Abstract: Cytoskeleton damage, particularly microtubule (MT) alterations, may play an important role in the pathogenesis of ischemia-induced myocardial injury. However, this disorganization has been scarcely confirmed in the cellular context. We evaluated MT network disassembly in myoblast cell line H9c2 and in neonatal rat cardiomyocytes in an in vitro substrate-free hypoxia model of simulated ischemia (SI). After different duration of SI from 30 up to 180 min, the cells were fixed and the microtubule network was revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…Oxidative stress is known to interfere with microtubule integrity and growth (33)(34)(35). Using HeLa cells, we performed confocal immunofluorescent detection of α-tubulin and EB1 ( Figure 3A).…”
Section: Cx43 and Eb1 Are Reduced At Intercalated Discs In Human End-mentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is known to interfere with microtubule integrity and growth (33)(34)(35). Using HeLa cells, we performed confocal immunofluorescent detection of α-tubulin and EB1 ( Figure 3A).…”
Section: Cx43 and Eb1 Are Reduced At Intercalated Discs In Human End-mentioning
confidence: 99%
“…There have been several reports of deleterious effects on the cardiomyocyte cytoskeleton, particularly in microtubules, as a result of ischemic and oxidative stress (33)(34)(35). Given the relatively short half-life of Cx43 hemichannels at the plasma membrane (36)(37)(38), their dependence on microtubules for delivery to the plasma membrane (18,19,24), and the diminished gap junction coupling associated with cardiac pathologies (3)(4)(5), we investigated whether forward trafficking of Cx43 was perturbed in the stressed/diseased myocardium, thus contributing to losses in cell-cell electrical coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Immunocytochemical staining was performed as described previously (Feng et al, 2007;Vandroux et al, 2004). Cells were cultured on coverslips (10-mm diameter) and rinsed twice in prewarmed (37°C) PBS.…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%
“…Recent studies have showed that in case of ischemia-reperfusion or oxygen-glucose deprivation, the MTs are more prone to hypoxic damage than the actin filaments (Sato et al, 1993). In addition, it is known that early disruption of the cytoskeleton ultrastructure correlates with the cellular reaction to a metabolic challenge (Hein et al, 1995;Vandroux et al, 2004), and thus promoting irreversible cell damage. It was reported that the homeostasis of MT forms relies on MT-associated proteins (MAPs) (Cassimeris, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Cytoskeletal damage, including MT alterations, has been linked with various pathological conditions. Disruption of the MT network has been reported in ischemia as an early ultrastructural change correlated with the cellular reaction to a metabolic challenge [11][12][13], and irreversible cell damage may be associated with the collapse of the MT cytoskeleton [14]. Proliferation of the MTs with taxol has been reported to protect against hypoxia/re-oxygenation injury [15], whereas the MT disruptor, colchicine, has been shown to abolish the protective effect of ischemic pre-conditioning [16,17].…”
Section: Introductionmentioning
confidence: 99%